2020
DOI: 10.1080/16549716.2020.1820714
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes of preterm babies during infancy in Eastern Uganda: a prospective cohort study

Abstract: Background Complications due to prematurity are a threat to child survival and full developmental potential particularly in low-income settings. Objective The aim of the study was to determine the neurodevelopmental outcomes among preterm infants and identify any modifiable factors associated with neurodevelopmental disability (NDD) Methods We recruited 454 babies (242 preterms with birth weight <2.5 kg, and 212 term babies) in a cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 34 publications
1
31
1
Order By: Relevance
“…In this systematic review and meta-analysis, the pooled mortality rate among preterm in East Africa was found to be 19.2%. This is consistent with the studies conducted in Asia, India, and Nigeria [ 48 , 49 , 51 ]. However, The mortality rate reported in this study is higher than studies reported from Germany [ 59 ], Iran [ 60 ], Australian [ 61 ], China [ 62 ], Libya [ 63 ], Mexico [ 64 ], Spain [ 65 ], and France 4.9% [ 66 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this systematic review and meta-analysis, the pooled mortality rate among preterm in East Africa was found to be 19.2%. This is consistent with the studies conducted in Asia, India, and Nigeria [ 48 , 49 , 51 ]. However, The mortality rate reported in this study is higher than studies reported from Germany [ 59 ], Iran [ 60 ], Australian [ 61 ], China [ 62 ], Libya [ 63 ], Mexico [ 64 ], Spain [ 65 ], and France 4.9% [ 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…The studies were conducted from 2012 to 2020 among more than 11 Eastern Africa countries including 12 from Ethiopia represented by 14 studies [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Tanzania [ 14 , 45 , 46 , 47 ] and Uganda [ 12 , 48 , 49 , 50 ] represented by 04 studies, Besides, Burundi [ 51 , 52 ] and Eretria [ 53 , 54 ] represented by 02 studies. While Malawi [ 55 ], Kenya [ 56 ], Zambia [ 24 ], Sudan [ 25 ], Mozambique [ 57 ], and Zimbabwe [ 58 ] are represented by 01 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children born small and sick are at higher risk of impaired growth and development and thus need more support to achieve their optimum developmental potential (World Health Organization, 2019). Studies on developmental delay and disability in the region amongst children born small and sick have shown anywhere from 20%–67% of children born small and sick surviving with developmental delay or disability (Boogaard et al, 2017; Kirk et al, 2017; Namazzi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Data in recent years have shown that adverse pregnancy outcomes such as preterm birth and LBW are the leading causes of under-5 mortality and neonatal death (Liu et al, 2015;Koffi et al, 2020;Dhaded et al, 2020). Additionally, premature and LBW infants are more likely to have complications such as neonatal jaundice (Platt, 2014), neonatal pneumonia (Shennan et al, 1988), neurodevelopmental disabilities (Namazzi et al, 2020) and other diseases. The increasing literature has demonstrated that preterm birth is associated with an increased risk for various diseases, including hypertension and kidney disease in adult life (Carmody and Charlton, 2013;de Jong et al, 2012;Reichetzeder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%